PATH RELATED MEAN CORDIAL GRAPHS - Murugan, A. Nellai (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Let G = (V, E) be a simple graph. G is said to be a mean cordial graph if Â f : V(G)â†’0,1,2 such that for each edge uv the induced map f* defined by f*(uv) = Â where Â denote the least integer which is â‰¤ x and |ef (0) - ef(1)| â‰¤ 1 where ef(0) is no.of edges with zero label. ef(1) is no.of edges with one label. The graph that admits a mean cordial labeling is called a mean cordial graph(MCG).In this paper , we proved that PnÊ˜K1, (Pn+K1) , Pn Ã— Pn,(Pn :C3) ,(Pn: S1) , Pn Ã—P2 ,Pn +2K1 Z-(Pn) are mean cordial graphs. Â Â Â Â Keywords : Mean cordial labeling, Mean cordial graph. 2000 Mathematics Subject Classification 05C78.